Anatomotopographic concepts: Round Table Wounds of the heart and large vessels of the thorax; introduction and coordinator Luis A Praderi - Bergalli, Luis (Cirugía del Uruguay, 1973)
Before going into the fundamental topics of this Table, we want to make a brief memory, anatomical, schematic and practical at the same time. The heart and great vessels are located in the mediastinal space, between both pleural cavities.